2012
DOI: 10.1177/0021998312469891
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid) nanocomposites with improved impact and thermal properties

Abstract: PLA nanocomposites containing 2 wt% of OMMT clay were prepared using twin screw extruder followed by injection moulding. EPR-g-MAH (5–20 phr) was used to improve the impact properties of PLA/OMMT nanocomposites. The mechanical properties of PLA nanocomposites were studied through tensile, flexural and impact tests. The morphology and dispersion of OMMT were examined using TEM and XRD. The thermal properties were characterised using differential scanning calorimetry and thermogravimetric analysis. The impact st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Thus, various approaches including copolymerization, plasticization, and blending with elastomeric materials have been carried out to enhance the impact properties and toughness of PLA . Recently, literatures showed that PLA can be toughened by maleated styrene‐ethylene/butylenes‐styrene, poly(ethylene glycol), maleic anhydride grafted ethylene‐propylene rubber, linear low density polyethylene, poly(ethylene glycol)‐functionalized polyhedral oligomeric silsesquioxane, poly(ε‐caprolactone) coated nano‐titania particles, and ultrafine full‐vulcanized powdered rubber …”
Section: Introductionmentioning
confidence: 99%
“…Thus, various approaches including copolymerization, plasticization, and blending with elastomeric materials have been carried out to enhance the impact properties and toughness of PLA . Recently, literatures showed that PLA can be toughened by maleated styrene‐ethylene/butylenes‐styrene, poly(ethylene glycol), maleic anhydride grafted ethylene‐propylene rubber, linear low density polyethylene, poly(ethylene glycol)‐functionalized polyhedral oligomeric silsesquioxane, poly(ε‐caprolactone) coated nano‐titania particles, and ultrafine full‐vulcanized powdered rubber …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Montmorillonite (by 2%wt) was found to improve the tensile modulus, flexural modulus, and tensile elongation of PLA, but could not improve the tensile strength and flexural strength. 16 However, montmorillonite was tested to improve the mechanical properties of TPU. 17 In the PLA/TPU blend matrix, the addition of montmorillonite increased the tensile strength and modulus but decreased the impact strength and elongation.…”
Section: Introductionmentioning
confidence: 99%
“…18 In thermal terms, the montmorillonite was mainly reflected in changing the crystallinity of PLA according to the differential thermal test. 16,19 The above reason is that the organically treated montmorillonite (OMMT) plays a role in connecting macromolecular segments in polymers during blending. Thus, the cross-sectional roughness of the composites becomes severe.…”
Section: Introductionmentioning
confidence: 99%
“…Maleated rubbers such as maleic anhydride grafted ethylene-propylene rubber (EPR-g-MAH) and maleic anhydride grafted styrene-ethylene/butylene-styrene copolymers (SEBS-g-MAH), has been used as polymeric compatibilizer, interfacial modifier and toughening agent. Recent reports have proved that the addition of EPR-g-MAH could enhance the dispersion of the nanoclay and improve the mechanical and thermal properties of various polymer nanocomposites, including polyamide 6/polypropylene/organoclay nanocomposites [11], PLA/clay nanocomposites [12][13][14].…”
Section: Introductionmentioning
confidence: 99%